2015
DOI: 10.4315/0362-028x.jfp-14-231
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Reported Handling of Raw Poultry Products at Home: Results from a National Survey

Abstract: Salmonella and Campylobacter cause an estimated combined total of 1.8 million foodborne infections each year in the United States. Most cases of salmonellosis and campylobacteriosis are associated with eating raw or undercooked poultry or with cross-contamination. Between 1998 and 2008, 20% of Salmonella and 16% of Campylobacter foodborne disease outbreaks were associated with food prepared inside the home. A nationally representative Web survey of U.S. adult grocery shoppers (n = 1,504) was conducted to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 40 publications
0
54
0
1
Order By: Relevance
“…32 In the USA, nearly 70% of consumers rinse raw poultry before cooking it and the majority of consumers (>80%) incorrectly store raw poultry in refrigerators. 33 This is extremely unsafe behaviour because of the potential cross-contamination of Campylobacter to other kitchen surfaces and other foods, especially ready-to-eat foods. 33 In the UK, outbreaks of Campylobacter infection are increasingly attributed to undercooked chicken livers, yet many recipes, including those of top chefs, advocate short cooking times and serving livers pink.…”
Section: Dangerous Consumer Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In the USA, nearly 70% of consumers rinse raw poultry before cooking it and the majority of consumers (>80%) incorrectly store raw poultry in refrigerators. 33 This is extremely unsafe behaviour because of the potential cross-contamination of Campylobacter to other kitchen surfaces and other foods, especially ready-to-eat foods. 33 In the UK, outbreaks of Campylobacter infection are increasingly attributed to undercooked chicken livers, yet many recipes, including those of top chefs, advocate short cooking times and serving livers pink.…”
Section: Dangerous Consumer Behaviourmentioning
confidence: 99%
“…33 This is extremely unsafe behaviour because of the potential cross-contamination of Campylobacter to other kitchen surfaces and other foods, especially ready-to-eat foods. 33 In the UK, outbreaks of Campylobacter infection are increasingly attributed to undercooked chicken livers, yet many recipes, including those of top chefs, advocate short cooking times and serving livers pink. 34 It is estimated that 19%-52% of livers served commercially in the UK fail to reach 70°C, and that predicted Campylobacter survival rates are 48%-98%.…”
Section: Dangerous Consumer Behaviourmentioning
confidence: 99%
“…If meat is handled and cooked properly, exposure to the pathogen is reduced. However, in many cases, people do not follow food preparation guidelines, thus increasing their risk of illness [32,33]. Kosa et al surveyed 1504 grocery shoppers in the USA and found that only 17 % of the consumers stored raw poultry on the bottom shelf of their refrigerators in a sealed container or plastic bag and only 62 % of the consumers owned a food thermometer [32].…”
Section: Contaminated Retail Meatmentioning
confidence: 99%
“…However, in many cases, people do not follow food preparation guidelines, thus increasing their risk of illness [32,33]. Kosa et al surveyed 1504 grocery shoppers in the USA and found that only 17 % of the consumers stored raw poultry on the bottom shelf of their refrigerators in a sealed container or plastic bag and only 62 % of the consumers owned a food thermometer [32]. Additionally, Bogard et al examined ground beef handling practices at 385 restaurants in eight states and reported that 77 % of the managers did not always measure the final cook temperature of hamburgers but instead used the appearance or texture of the hamburgers as an indicator of being "done," and 62 % of the restaurants had employees who did not wash their hands between handling raw ground beef and ready to eat foods [33].…”
Section: Contaminated Retail Meatmentioning
confidence: 99%
“…Reviews of general food safety practices by consumers have stressed the importance of educating the consumer (2) and sometimes have found different results from surveys in comparison to observational studies (3). Studies on USA consumer purchase (4)(5), preparation (6), and storage practices (7)(8) have found that educated consumers are more likely to engage in risky food handling practices. Income, age, race, and gender are commonly collected demographics that could predict behavior characteristics.…”
Section: Introductionmentioning
confidence: 99%